2016
DOI: 10.1080/09658211.2016.1182553
|View full text |Cite
|
Sign up to set email alerts
|

The organisation of spatial and temporal relations in memory

Abstract: Episodic memories are comprised of details of "where" and "when"; spatial and temporal relations, respectively. However, evidence from behavioural, neuropsychological, and neuroimaging studies has provided mixed interpretations about how memories for spatial and temporal relations are organised-they may be hierarchical, fully interactive, or independent. In the current study, we examined the interaction of memory for spatial and temporal relations. Using explicit reports and eye-tracking, we assessed younger a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 64 publications
0
23
3
Order By: Relevance
“…Differences in the ability to verbally code spatial and temporal information may explain why the findings of the present research seem inconsistent with the findings from Rondina and colleagues [ 33 ] who examined the relations between temporal and spatial features using a short-term memory paradigm. Adults were presented with triplets of non-nameable objects at different locations on a computer screen and after a 2 second delay, were presented with the triplets such that the spatial and temporal relations between the objects were the same (i.e., same spatial configuration between the objects, and same temporal order), or were manipulated (i.e., spatial relations were manipulated, temporal relations were manipulated, or both the spatial and temporal relations were manipulated).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Differences in the ability to verbally code spatial and temporal information may explain why the findings of the present research seem inconsistent with the findings from Rondina and colleagues [ 33 ] who examined the relations between temporal and spatial features using a short-term memory paradigm. Adults were presented with triplets of non-nameable objects at different locations on a computer screen and after a 2 second delay, were presented with the triplets such that the spatial and temporal relations between the objects were the same (i.e., same spatial configuration between the objects, and same temporal order), or were manipulated (i.e., spatial relations were manipulated, temporal relations were manipulated, or both the spatial and temporal relations were manipulated).…”
Section: Discussioncontrasting
confidence: 99%
“…First, evidence of an influence of the mental timeline in long-term memory for events would add to the literature on the relation between space and time in the mind [ 32 ]. Second, evidence of different developmental trajectories for spatial and temporal memory, and/or different influences of the spatiotemporal mental timeline on memory for spatial location and temporal order would impact our understanding of the organization of spatial and temporal components of the episodic memory system [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus and the broader MTL mediate the formation of lasting memory representations for items, as well as their relative spatial locations and temporal orderings, which can then provide the guidance to the oculomotor system regarding precise localization of where to look and in what order . Multiple regions across occipital, frontal, and parietal lobes showed observable responses following hippocampal/MTL stimulation, suggesting that there is not one single region that may provide, or contribute to, the transformation of information.…”
Section: Network Connectivity and Dynamicsmentioning
confidence: 99%
“…In the literature, eye movements have been strongly implicated in memory encoding and retrieval; for example, limiting the number of fixations appears to be detrimental for both, when compared to free-viewing conditions (Henderson et al 2005;Johansson and Johansson 2014). Moreover, altered fixation patterns in older adults have been proposed to be functionally linked to memory deficits (Chan et al 2011;Hannula et al 2007;Olsen et al 2015;Ryan et al 2000;Rondina et al 2017;Shih et al 2012;Voss et al 2011). Consistently, we found that gaze direction distributions differed significantly between young and old observers during both the exploration and the probe trials (although we did not find any difference in the sheer number of fixations made; results not shown).…”
Section: On Eye Movementsmentioning
confidence: 99%